The Role of Play In Improving Young Children's Speaking Abilities - Rita Prima Bendriyanti (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
It is necessary to take action because the speaking abilities of the youngsters at Baitul Hikmah Early Childhood Education have declined. The purpose of this study is to enhance young children's speaking skills in early childhood education by using role-playing exercises. The John Elliot model of classroom action research is applied in this study methodology. Teachers, parents, and kids in Baitul Hikmah 1 Early Childhood Education are the subjects of this study. There are nine males and eleven girls among the twenty children. Data for this study were gathered through observation, interviews, and documentation. The researcher observed the children at Baitul Hikmah Early Childhood Education 1 and their speaking ability. Both quantitative and qualitative analysis were employed to analyze the data for this study. The study's findings demonstrate that playing activities can help Baitul Hikmah 1 Early Childhood Education students' speaking abilities.